A Stimulation Function of Synaptotagmin-1 in Ternary SNARE Complex Formation Dependent on Munc18 and Munc13 - Li, Yun; Wang, Shen; Li, Tianzhi; Zhu, Le; Xu, Yuanyuan; Ma, Cong (Frontiers in Molecular Neuroscience, 2017)
The Ca2+ sensor synaptotagmin-1 (Syt1) plays an essential function in synaptic exocytosis. Recently, Syt1 has been implicated in synaptic vesicle priming, a maturation step prior to Ca2+-triggered membrane fusion that is believed to involve formation of the ternary SNARE complex and require priming proteins Munc18-1 and Munc13-1. However, the mechanism of Syt1 in synaptic vesicle priming are still unclear. In this study, we found that Syt1 stimulates the transition from the Munc18-1/syntaxin-1 complex to the ternary SNARE complex catalyzed by Munc13-1. This stimulation can be further enhanced in a membrane-containing environment. Further, we showed that Syt1, together with Munc18-1 and Munc13-1, stimulates trans ternary SNARE complex formation on membranes in a manner resistant to disassembly factors NSF and α-SNAP. Disruption of a proposed Syt1/SNARE binding interface strongly abrogated the stimulation function of Syt1. Our results suggest that binding of Syt1 to an intermediate SNARE assembly with Munc18-1 and Munc13-1 is critical for the stimulation function of Syt1 in ternary SNARE complex formation, and this stimulation may underlie the priming function of Syt1 in synaptic exocytosis.